Kemandirian Penyelenggara Pemilihan Umum (Kajian terhadap Putusan Mahkamah Konstitusi No. 81/PUU-IX/2011) - Riri Nazriyah (Fakultas Hukum Universitas Islam Indonesia, 2011)
That one of the requirement to be and Board of Election Supervisory member is to resign from political party at the time of registration. The regulation is assumed contradicted to Constitution because it may hamper the independency of Election Committee. Therefore judicial review on that Act was submitted to Constitution Court. How is the consideration in deciding the judicial review request of Article 11 (i) and Article 85 (i) of Act No. 15 of 2011.This research is normative in form of prescriptive research. The used approaches are legislation approach and case approach. The data used in this research is secondary data. The source from secondary data already covers primary, secondary, and tertiary legal materials.The result of the research shows that according to Constitutional Court, in Article 11 (i) and Article 85 (i) of Act No. 15 of 2011 as long as the phrase “to resign from the political party membership at the time of candidate registration” is contradicted to Article 22E (5) of Constitution so long as not interpreted as “at least in period of 5 years has resigned from the political party membership at the time of registering as candidate.”